Adoption and Value of the Medicare Annual Wellness Visit: A Mixed-Methods Study. (August 2023) - Hamer, Mika K.; DeCamp, Matthew; Bradley, Cathy J.; Nease, Donald E.; Perraillon, Marcelo C.
Medicare's Annual Wellness Visit (AWV) was introduced in 2011 to encourage the utilization of preventive services, but many clinicians and patients still do not participate in the visit. We qualitatively and quantitatively assessed motivations and clinical and financial value of AWVs from a primary care perspective using interviews and Medicare claims from 2012 to 2019. Primary care providers with the highest acuity patients had AWV utilization rates 11.2 percentage points lower than providers with the lowest acuity patients; utilization rates were 3.8 percentage points lower in rural counties. Adoption was motivated by patient needs and financial incentives. AWVs closed gaps in preventive care, strengthened patient–provider relationships, facilitated advance care planning, and provided an opportunity to improve quality metrics. Overall, the AWV has the potential to increase the use of high-value preventive services although not all clinics have an economic incentive to adopt the visit, which may explain some of the variability in utilization rates.